Advanced chickpea lines resistant against fusarium wilt (Fusarium oxysporum) - JHA, UDAY CHAND; SAABALE, PARASAPPA RAJAPPA; L, MANJUNATHA; CHATURVEDI, SUSHIL K; SINGH, NARENDRA PRATAP (The Indian Journal of Agricultural Sciences, 2021)
Fusarium wilt (FW) disease caused by Fusarium oxysporum f. sp. ciceris remains one of the major biotic stresses challenging chickpea production globally. Thus, to explore FW resistant chickpea genotypes; we tested a set of 75 advanced breeding lines including one FW susceptible check and one FW resistant check for two consecutive years 2016 and 2017 in FW (Foc2) infected sick plot. A total of 30 resistant lines, viz. IPC2005-45, IPC2005-19,IPC2010-03 and 34 moderately resistant, viz. IPC 2005-37, IPC 2004-08, IPC 2006-64 and 11 susceptible lines were identified based on the two year data. Thus, these identified resistant lines could be directly released for FW resistant variety or could serve as important donors for developing FW resistant chickpea cultivars.